2021
DOI: 10.1124/jpet.121.000518
|View full text |Cite
|
Sign up to set email alerts
|

circ-Keratin 6c Promotes Malignant Progression and Immune Evasion of Colorectal Cancer through microRNA-485-3p/Programmed Cell Death Receptor Ligand 1 Axis

Abstract: Background: Recently, circular RNA (circRNA) was reported to be a significant participant in the development of tumorigenesis, including colorectal cancer. Therefore, we aimed to clarify the precise role of circ-keratin 6C (circ-KRT6C) in colorectal cancer progression. Methods: The relative expression levels of circ-KRT6C, microRNA-16-5p (miR-485-3p), and programmed cell death receptor ligand 1 (PDL1) were analyzed by real-time quantitative polymerase chain reaction and western blot assays. The proliferation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…For evaluation of the association between immune checkpoints and hsa_circ_0000190, relevant ligands were selected, such as CD80/CD86, which interacted with CTLA-4 and CD28 for T-cell inhibition or activation, respectively. The other immune checkpoints included TIM-3, BTLA, TIGIT, LAG-3, and PD-1, and the related binding partners were galectin-9, HVEM, PVR (CD155), HLA-DR, and PD-L1, respectively [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For evaluation of the association between immune checkpoints and hsa_circ_0000190, relevant ligands were selected, such as CD80/CD86, which interacted with CTLA-4 and CD28 for T-cell inhibition or activation, respectively. The other immune checkpoints included TIM-3, BTLA, TIGIT, LAG-3, and PD-1, and the related binding partners were galectin-9, HVEM, PVR (CD155), HLA-DR, and PD-L1, respectively [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have reported the role of circRNAs in regulating the expression of PD-L1 through circRNA–miRNA–mRNA axis. A number of circRNAs, such as circBART2.2, hsa_circ_0136666, circ-keratin 6c, CDR1-AS, circ-VIM, hsa_circ_0003288, CircCHST15, circ-CPA4, hsa-circRNA-002178, and Circ_0000284 were shown to affect PD-L1 expression, leading to tumor immune escape in various types of cancers, including nasopharyngeal carcinoma, colorectal cancer, esophageal cancer, hepatocellular carcinomas (HCC), and lung cancer [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Our previous study discovered the correlation between hsa_circ_0000190 plasma level and PD-L1 level in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has shown that utilization of immune checkpoints by cancer cells is important for immune evasion ( 85 ). Recently, Jiang et al ( 86 ) revealed the association between circRNAs and immune evasion in CRC. It was demonstrated that circ-keratin 6C (KRT6C), which is encoded from the KRT6C gene, functioned as a miR-485-3p sponge and promoted immune evasion by upregulating programmed cell death receptor ligand 1, which is the ligand for the immune check point programmed cell death protein 1 ( 86 ).…”
Section: Circrnas Are Possibly Involved In Immune Evasionmentioning
confidence: 99%
“…Recently, Jiang et al ( 86 ) revealed the association between circRNAs and immune evasion in CRC. It was demonstrated that circ-keratin 6C (KRT6C), which is encoded from the KRT6C gene, functioned as a miR-485-3p sponge and promoted immune evasion by upregulating programmed cell death receptor ligand 1, which is the ligand for the immune check point programmed cell death protein 1 ( 86 ). This suggests the possible role of circRNAs in immune regulation and immune evasion.…”
Section: Circrnas Are Possibly Involved In Immune Evasionmentioning
confidence: 99%
“… 19 Consistently, circ‐KRT6C promoted malignant progression and immune evasion of colorectal cancer via acting as a miR‐485‐3p sponge. 21 Recently, increasing evidence has revealed that many circRNAs are also differently expressed between non‐degenerated and degenerated NP tissues, 22 indicating their potential functions in the development of IVDD. Although some circRNAs have been revealed diverse functions in the regulation of IVDD, 23 the role and underlying mechanisms of circRNAs in IVDD largely remain vague and need further investigation.…”
Section: Introductionmentioning
confidence: 99%